Front Cover. Issue 3 (9th February 2020) - Wang, Jianjun; Legendre, Pierre; Soininen, Janne; Yeh, Chih‐Fu; Graham, Emily; Stegen, James; Casamayor, Emilio O.; Zhou, Jizhong; Shen, Ji; Pan, Feiyan
Abstract : The cover image is based on the Original Article* Temperature drives local contributions to beta diversity in mountain streams: Stochastic and deterministic processes by JIANJUN WANG** et al., https://doi.org/10.1111/geb.13035 .***